The most lethal virus: the need for an adequate fake news regulation in Peru - St. Laurent del Castillo, Jacqueline Rose (2021)
New technologies have led to a 180 degree turn in the way society shares, consumes and accesses information. However, just as the media has contributed to personal and social development, the panorama in recent years has changed as a result of the growing wave of false information on the internet.In this article, the authors determine the risks involved in spreading fake news about the COVID-19 pandemic and assess whether current national legislation, based on what international parameters have established, manages to mitigate this issue that has forced even the most developed legislations in the world to modify the scope and effects of their regulations.